Genome-wide association meta-analysis of human olfactory identification discovers sex-specific and sex-differential genetic variants - Förster, Franz; Emmert, David; Horn, Katrin; Pott, Janne; Frasnelli, Johannes; Imtiaz, Mohammed Aslam; Melas, Konstantinos; Talevi, Valentina; Chen, Honglei; Engel, Christoph; Filosi, Michele; Fornage, Myriam; et al. (Nature communications, 2025)
Smelling is a human sense, expressing strong sexual dimorphisms. We aim to improve the knowledge of the genetics of human olfactory perception by performing an exploratory genome-wide association meta-analysis of up to 21,495 individuals of European ancestry. By sex-stratified and overall analysis of the identification of twelve odours and an identification score, we discovered ten independent loci, seven of them novel, with trait-wise genome-wide significance ( p < 5 × 10 −8 ) involving five odours. Seven of these loci, including four novel ones, are also significant using a stricter study-wide significance threshold ( p < 3.85 × 10 − 9 ). Loci were predominantly located within clusters of olfactory receptors. Two loci were female-specific while one was sex-differential with respective candidate genes containing androgen response elements. Two-sample Mendelian randomization was applied to search for causal relationships between sex hormones, odour identification and neurodegenerative diseases. A causal negative effect was detected for Alzheimer’s disease on the identification score. These findings deepen our understanding of the genetic basis of olfactory perception and its interaction with sex, prioritizing mechanisms for further molecular research. Olfactory perception shows marked sexual dimorphism, yet its genetic basis remains underexplored. Here, the authors show sex-specific and shared genetic loci for odour identification, implicating olfactory receptor clusters and links to Alzheimer’s disease risk.